Effects of fatty acid chain length on properties of potato starch–fatty acid complexes under partially gelatinization. Issue 1 (1st January 2018) - Wang, Lan; Wang, Wei; Wang, Yiwen; Xiong, Guangquan; Mei, Xin; Wu, Wenjing; Ding, Anzi; Li, Xin; Qiao, Yu; Liao, Li
ABSTRACT: A series of starch–fatty acid samples were prepared using potato starch and four fatty acids differing in their chain length, including lauric (C12), myristic (C14), palmitic (C16), and stearic (C18) acids. The results indicated that the fatty-acid chain length played a significant role in altering the properties of potato starch–fatty acid complexes. The complexing index of potato starch–fatty acid complexes decreased from 0.38 to 0.18 with increasing carbon-chain length. V-type crystalline polymorphs were formed between starch and four fatty acids, with shorter chain fatty acids preserving more crystalline structure. X-ray diffraction studies revealed that the degree of crystallinity exhibited by the starch samples was dependent on the fatty-acid chain length. In the Fourier transformed infrared spectrum of the samples, the new spikes at 2917, 2850, 1018, and 720 cm −1 were assumed to be related to the presence of fatty long chains. The formation of amylose–fatty acid complex inhibited granule swelling of potato starch, wlonger chain fatty acids showing greater inhibition. Scanning electron microscopy microscopic examination indicated that amylose–fatty acid interactions taken place during starch gelatinization retarded the destruction of the granules.